Investigating the role of FOX gene family in development and stress response in Labeo rohita: A multi-faceted analysis of phylogeny and genome characterization - Saima Naz; Urwah Ishaque; Ahmad Manan Mustafa Chatha; Muhammad Farooq; Qudrat Ullah; Shabana Naz; Marco Ragni; Ibrahim Alhidary (PLoS ONE, 2025)
The forkhead box (FOX) gene family of transcription factors regulates muscle development, immune responses, and metabolic processes across species. Despite extensive studies on FOX genes in other organisms, their evolutionary and functional roles in Labeo rohita, an economically and ecologically important freshwater fish, remain unclear. Owing to its unique physiological and ecological traits, L. rohita is an ideal model for exploring these roles. Here, we present the first computational analysis of the FOX gene family in L. rohita, identifying 21 FOX genes. Physicochemical analysis revealed that most FOX proteins have a basic nature except for FOX A3, D3, I2, O1, O3, O4, P1, and P2. Instability index analysis indicated that all FOX proteins are unstable (values > 40), while hydrophobicity assessment showed that except FOX O1, all proteins are hydrophobic. Phylogenetic analysis grouped FOX homologs into 11 major clades with other vertebrates. All proteins exhibited structural homogeneity by sharing the Forkhead Box domain. Gene structure comparisons revealed seven duplicated pairs, and Circos analysis demonstrated organization into 20 clusters. This study highlights the critical roles of FOX genes and fills a significant knowledge gap, providing a foundation for future functional and phylogenomic studies with implications for aquaculture and evolutionary biology.